Self-Efficacy and Self-Regulation as Predictors of University Students’ Mathematics Learning Achievement - Anggraini Anggraini; Nurul Afiyah; Gandung Sugita; Mustamin Idris (Universitas Lambung Mangkurat, 2026)
Learning achievement in mathematics at the university level is influenced by various internal factors, including students’ beliefs in their abilities and their capacity to regulate learning processes. This study aims to examine the effects of self-efficacy and self-regulation, both individually and simultaneously, on university students’ mathematics learning achievement. An ex post facto quantitative design was employed involving 98 mathematics education students selected through proportional random sampling from a population of 130 students. Data were collected using self-efficacy and self-regulation questionnaires, as well as students’ grade point averages from first- and second-semester mathematics courses as indicators of learning achievement. The data were analyzed using simple and multiple linear regression after meeting classical assumption requirements. The results indicate that self-efficacy has a significant effect on mathematics learning achievement, contributing 15.5% of the variance, while self-regulation contributes 13.1%. When analyzed simultaneously, both variables significantly influence learning achievement with a combined contribution of 16.7%. Despite their statistical significance, the magnitude of these effects is relatively modest, suggesting that mathematics learning achievement is shaped by a combination of internal and external factors beyond self-efficacy and self-regulation alone. These findings imply that efforts to improve students’ mathematics achievement should not only focus on strengthening self-efficacy and self-regulation but also be supported by effective instructional strategies, learning environments, and institutional support. This study provides empirical evidence for mathematics educators to design learning interventions that integrate psychological and pedagogical approaches in higher education contexts.